Forest fire management practices in Peninsular Malaysia - Nuruddin, Ahmad Ainuddin; Hamzah, Mohd Basri; Abu Bakar, Mohd Fauzi (1989)
A study on fire management practices in plantation was conducted in forest plantation areas and in selected rubber plantations. The objectives of this study were to examine and compare fire management practices in selected forest and rubber plantations and to look into problems related to fire management of these areas. The methods used were survey questionnaire and interview with relevant authorities. The questionnaire mainly touch on general information of plantations past incidences of fires, fire prevention measures and practices, cost and equipments in fire management, fire fighting capability and problems faced by the forest plantation. The results describe the current state of forest fire management practices in Peninsular Malaysia. Of these, two aspects of management were shown to need the most improvement i.e training and equipments.